2022
DOI: 10.1155/2022/9177545
|View full text |Cite
|
Sign up to set email alerts
|

Association of BIRC5 Gene Polymorphism with the Collateral Circulation and Severity of Large Artery Atherosclerotic Stroke

Abstract: Objectives. The collateral circulation near the cerebral artery occlusion can contribute to the relief of the symptoms and signs of stroke. Genetic factors play a decisive role in the difference in collateral circulation. Survivin, encoded by the baculoviral inhibitor of apoptosis (IAP) repeat-containing 5 gene (BIRC5), plays an important role in maintaining long-term endothelial integrity and homeostasis and as an angiogenic factor in the treatment of vascular diseases. We hypothesized that genetic variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Numerous studies have also shown that BIRC5 overexpression is associated with angiogenesis and inhibition of cell apoptosis in lung cancer, thus making it a potential anti-NSCLC therapeutic biomarker [21][22][23][24]. As an angiogenic factor, BIRC5 sustains prolonged vascular endothelial cell integrity [25], and, hence, influences treatment responses in vascular diseases [26]. The growth of new vascular networks is crucial, since cancer progression depends on it for a sufficient supply of oxygen and nutrients [27].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also shown that BIRC5 overexpression is associated with angiogenesis and inhibition of cell apoptosis in lung cancer, thus making it a potential anti-NSCLC therapeutic biomarker [21][22][23][24]. As an angiogenic factor, BIRC5 sustains prolonged vascular endothelial cell integrity [25], and, hence, influences treatment responses in vascular diseases [26]. The growth of new vascular networks is crucial, since cancer progression depends on it for a sufficient supply of oxygen and nutrients [27].…”
Section: Introductionmentioning
confidence: 99%